A communication model for the employee creativity in the context of sustainability and organizational culture - Jakubauskytė-Andriulienė, Viktorija (Creativity Studies, 2024)
Creativity is a key competence of present and future-oriented employees of the business organisations, as well as a prerequisite for the success of the companies. By conducting a comprehensive literature review this article discusses on the concept of creativity in organisations, the role of communication in managing the expression of employee creativity. Furthermore, in response to the contemporary needs of organisations to comply with the legal requirements based on the European Union directives on the integration of sustainability into the activities of organisations, the article also examines the concept of sustainability and its intersection with the organisational culture of companies and communication. The communication model developed on the basis of the theoretical assumptions includes empowering, managing and engaging communication, through which the organisational culture promotes the creative expression of employees and their involvement in the implementation of sustainability practices in organisations. In addition, the integration of sustainability as a distinct theme and strategic direction into the organisational culture is also noted and embedded.